Cell Adherence Competition between Osteoblasts and Fibroblasts on Various Materials Influences the Establishment of Osseointegration - Tamai, Miho; Harimoto, Kenichi; Nagaoka, Noriyuki; Yoshihara, Kumiko; Yoshida, Yasuhiro; Tagawa, Yoh-ichi (Archives of Clinical and Biomedical Research, 2021)
Osseointegration is a key factor in determining the success of a prosthetic implant. Titanium and its alloys are widely used as implantable materials because of good adaptation and connection to bone tissues, known as osseointegration. We focused on the invasion of fibrous tissue into the bone tissue–material interface and hypothesized that there might be competition for cell adhesion between osteoblasts and fibroblasts on the material surface. In this study, we established a cell competition model in a co-culture of osteoblasts and fibroblasts under shear stress conditions to elucidate fibroblast-associated failure of osseointegration after implantation. The osteoblasts adhere better on titanium than fibroblasts under shear stress conditions. The alkaline phosphatase–positive cells were increased when osteoblasts were co-cultured with fibroblasts, suggesting that the small population of fibroblasts promotes osteoblast differentiation through the production of extracellular matrices including type I collagen. Cell adhesion competition created a balance of osteoblasts and fibroblasts on the implant material surface in the initial stage of osseointegration resulting in a high osseointegration ratio. These results show that fibroblasts are able to both inhibit osseointegration and help adhesion and differentiation of osteoblasts by producing type I collagen.